The allure of the private practitioner: Is this the only alternative for the urban poor in India? - Nupur Barua; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2011)
The main objective of the study has been to identify trajectories of health seeking behaviour of the urban poor, particularly their use of the private health sector, with the aim to identify strategies to improve quality of health care for this burgeoning population. This article presents findings from a slum settlement in Delhi where ethnographic sub-studies were carried out over two years among private health providers and selected households alongside a survey of household expenditure patterns. The primary research tools were in-depth interviews with practitioners and key informants as well as observations of clinical interactions. Illness narratives and case studies were documented over two years. The software package q.s.r. Nvivo was used for coding and content analysis. It was found that almost 90% of the respondents exclusively depend on local unlicensed and unregistered practitioners for basic primary health care. Long distances, time-consuming procedures, rude behaviour and, in many cases, bribes that had to be paid to staff in the hospitals were cited as major deterrents to utilising government facilities. Despite the public health consequences of inappropriate treatment protocols and misuse of drugs by these untrained private providers, in the absence of a structured urban primary health care system in the country, they seem to be the only alternative for the burgeoning urban poor in vast metros such as Delhi.